On the Double-Object Construction in Modern Chinese and Analysis of Errors by Thai Learners - Bai, Fen (Journal of Sinology (วารสารจีนวิทยา), 2017)
This article focuses on the issues related with the double-object construction in modern Chinese. It gives a brief comparison on the double-object constructions in Chinese and Thai language. Meanwhile with questionnaire surveys in Thailand, I obtain the errors of Thai learners. It also probes into the presentation of double-object construction grammar and hierarchy of difficulty. I combined with theories related to pedagogical grammar. I put forward some teaching and learning uggestions concerning the pedagogy of the double-object construction for Thai learners.